دور اللامنهجية العربية في تعليم اللغة العربية في المدرسة الثانوية الحكومية الإسلامية الواحدة بلانجكات - Syahfira, Cut Nadia; Haq, Samsul (MANAZHIM, 2024)
Difficulties in learning Arabic become an obstacle in the learning process, such as lack of time, place and learning methods. This research aims to determine the Arabic language learning process in Arabic extracurriculars and to determine the role of Arabic extracurriculars in Arabic language learning at MAN 1 Langkat. The method used in this research uses a qualitative approach with descriptive methods through observation, interviews and documentation and data analysis techniques using the Miles & Huberman theory, namely data reduction, data presentation and drawing conclusions. The results of this research are that the Arabic language learning process in the MAN 1 Langkat Arabic extracurricular is carried out once a week with several activities such as Arabic content, Arabic games, Imla', Muhadharah, Muhadatsah, Drama and questions and answers at the Arabic language olympiad using the discussion method through learning media in the form of cellphones, dictionaries and books. The existence of the Arabic extracurricular role makes students interested in learning Arabic and makes it easier for students to understand Arabic language learning as well as improving learning outcomes and achieving many achievements in several branches of Arabic language competitions.